An anomaly in persistent right umbilical vein of portal vein diagnosed by ultrasonography - Nakanishi, Shigeo (World J Gastroenterol, 2005)
AIM: To detect the anomaly in the persistent right umbilical vein (PRUV) of portal vein (PV) with deviation of the ligamentum tere and left-sided gallbladder. METHODS: A total of 5783 candidates for routine analysis were evaluated for hepatic vascular abnormalities by ultrasonography. RESULTS: Ten candidates (0.17%) had a portal vein anomaly with a rightward-deviated ligamentum tere. The blood-flow velocity in the PRUV of the portal vein (17.7±3.0 cm/s) of the 10 cases was similar to that of the right anterior portal trunk (17.6±4.1 cm/s). However, the vessel diameter of the PRUV (φ12.4±4.4 mm) was larger than the right anterior portal trunk (j6.1±0.9 mm). Therefore, flow volume in the anomalous portion (0.97±0.30 L/min) was more than that in the right anterior portal trunk (0.18±0.05 L/min). CONCLUSION: The anomaly plays an important role in intra-hepatic PV flow.